2019
DOI: 10.3390/cancers11060778
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR as a Prognostic Predictor for Diverse Human Cancers: A Meta- and Bioinformatics Analysis

Abstract: Several studies suggest that upregulated expression of the long non-coding RNA HOX transcript antisense RNA (HOTAIR) is a negative predictive biomarker for numerous cancers. Herein, we performed a meta-analysis to further investigate the prognostic value of HOTAIR expression in diverse human cancers. To this end, a systematic literature review was conducted in order to select scientific studies relevant to the association between HOTAIR expression and clinical outcomes, including overall survival (OS), recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 102 publications
1
11
0
Order By: Relevance
“…Not much is known about the 9 noncoding genes we identified as FOXA1 targets, with the exception of the lncRNA HOTAIR. Similar to our findings on FOXA1's role in inhibiting anoikis, which, in turn, would promote metastasis, three of the nine identified targets, LINC00365, HNF1A-AS1, and HOTAIR, were previously implicated in promoting metastasis (50,61,62). In contrast, RPLP0P2 and LINC00589 have been shown to inhibit metastasis in lung cancer (59,63), although their role in CRC remains unknown.…”
Section: Discussionsupporting
confidence: 86%
“…Not much is known about the 9 noncoding genes we identified as FOXA1 targets, with the exception of the lncRNA HOTAIR. Similar to our findings on FOXA1's role in inhibiting anoikis, which, in turn, would promote metastasis, three of the nine identified targets, LINC00365, HNF1A-AS1, and HOTAIR, were previously implicated in promoting metastasis (50,61,62). In contrast, RPLP0P2 and LINC00589 have been shown to inhibit metastasis in lung cancer (59,63), although their role in CRC remains unknown.…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, Li et al reported this lncRNA was upregulated in liver of two T2DM murine models (db/db and C57BL/6J mice) treated with high-fat diet ( 49 ). Hotair is located within the HOMEOBOX C ( HOXC ) gene cluster on chromosome 12q13.13 and is involved in cellular proliferation, inhibition of apoptosis, genomic instability, angiogenesis, and metastasis ( 90 92 ). Moreover, Hotair upregulation promotes hepatic insulin resistance via the Akt/GSK pathway ( 38 ), which might partially explain its association with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that HOTAIR expression was significantly increased in cancer tissues compared with that in normal tissues, and its expression level was a risk factor for OS in patients with cervical cancer [37]. Several other studies also found similar results [38][39][40]. Moreover, there was an obvious relationship between high expression of HOTAIR and clinicopathological parameters, such as venous invasion, advanced tumor infiltration and distant metastasis.…”
Section: Discussionmentioning
confidence: 84%